2018
DOI: 10.1186/s12889-018-6246-3
|View full text |Cite
|
Sign up to set email alerts
|

Who is in the near market for bicycle sharing? Identifying current, potential, and unlikely users of a public bicycle share program in Vancouver, Canada

Abstract: BackgroundPublic bicycle share programs in many cities are used by a small segment of the population. To better understand the market for public bicycle share, this study examined the socio-demographic and transportation characteristics of current, potential, and unlikely users of a public bicycle share program and identified specific motivators and deterrents to public bicycle share use.MethodsWe used cross-sectional data from a 2017 Vancouver public bicycle share (Mobi by Shaw Go) member survey (n = 1272) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
3
11
1
Order By: Relevance
“…The results reveal that just under 30% of the respondents used MBSS for more than one year, which may be an indicator of a low level of loyalty to MBSS and could be result of low level of system service quality. Most of the users in our study have a low to medium income, in contrast to other previous studies on BSSs which showed higher rates of adoption among higher income residents (Transport for London, 2010; Ogilvie and Goodman, 2012;Fishman et al, 2014;Fishman et al, 2015;Ricci, 2015;Raux et al, 2017;Hosford et al, 2018). The differences between BSSs in developing and developed countries in terms of users' income was discussed recently by Jahanshahi et al (2019b), where it seems using a BSS is more reasonable in developing countries and contexts which have higher costs associated with of transportation and cars.…”
Section: Discussioncontrasting
confidence: 63%
“…The results reveal that just under 30% of the respondents used MBSS for more than one year, which may be an indicator of a low level of loyalty to MBSS and could be result of low level of system service quality. Most of the users in our study have a low to medium income, in contrast to other previous studies on BSSs which showed higher rates of adoption among higher income residents (Transport for London, 2010; Ogilvie and Goodman, 2012;Fishman et al, 2014;Fishman et al, 2015;Ricci, 2015;Raux et al, 2017;Hosford et al, 2018). The differences between BSSs in developing and developed countries in terms of users' income was discussed recently by Jahanshahi et al (2019b), where it seems using a BSS is more reasonable in developing countries and contexts which have higher costs associated with of transportation and cars.…”
Section: Discussioncontrasting
confidence: 63%
“…Another key contribution of this paper is the focus on lower-income individuals living in an urban area where there is a deliberate expansion of bikeshare bikes and docks. Consistent with previous literature ( Fishman et al, 2014 , Ogilvie and Goodman, 2012 , Hosford et al, 2018 ); bikeshare users in our sample differed significantly from non-users with regard to age, sex and race, as well as employment and student status. These sociodemographic differences between bikeshare users and non-users highlight a continuing need for a focus on equity when promoting and expanding bikeshare programs in the future.…”
Section: Discussionsupporting
confidence: 91%
“…For both users and non-users, the most frequently cited barriers included: safety concerns, lack of a helmet, proximity to stations, trouble with renting/returning a bike, and weather, all of which are consistent with previous literature ( Nickkar et al, 2018 , McNeil et al, 2017 , Fishman et al, 2014 , Fishman, 2016 , Hosford et al, 2018 ). The main facilitators were also consistent with existing literature as well as between the two groups of users, and included: convenience, proximity to docking stations, environmental benefits, economic benefits, fun, and health benefits ( Nickkar et al, 2018 , McNeil et al, 2017 , Fishman et al, 2014 , Fishman, 2016 , Hosford et al, 2018 ). The similarity in barriers and facilitators across users and non-users is notable, and may suggest that addressing these barriers could increase participation and satisfaction among both groups.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations